Ternary precursors, methods of making the same, and batteries

CN122977463APending Publication Date: 2026-10-27YIBIN GUANGYUAN LITHIUM BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611259068.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

随着电池对高容量和长循环寿命的双重需求日益迫切,这种常规均一结构暴露出了严重的局限性:一是对于不同粒径的前驱体,若其内部一次颗粒堆积过密,会延长锂离子的固相扩散路径,导致高倍率下材料深层的活性位点无法有效释放,极大地限制了放电容量;二是三元材料在充放电时,常伴随着剧烈的各向异性晶格应变,常规无序堆积或均一形貌的一次颗粒在应力传导时极易产生应力集中,导致二次颗粒内部出现放射状开裂,加速电解液渗透、加剧过渡金属溶出,最终表现为电池容量快速衰减和循环性能恶化,引发副反应,使容量性能急剧崩塌

Benefits of technology

本发明实施方式提供的三元前驱体属于高容量性三元前驱体,其通过在三元前驱体二次颗粒的内部构建自内向外L/d呈阶梯式递增的多层形貌梯度结构,随着二次颗粒的粒径增大,一次颗粒的层数同步增多。其中,最内层的一次颗粒建立起应力缓冲带,在源头上抑制微裂纹的出现,显著降低充放电过程中的颗粒开裂率;中间层的一次颗粒保障了锂离子在深层材料中的快速传输,有效提升正极材料放电容量;最外层的一次颗粒则有利于促进离子传输。本发明通过多级缓冲结构,自发形成高孔隙离子传输通道,极大缩短锂离子扩散路径,提升产品容量。确保了不论大颗粒还是小颗粒,均能在保持宏观形貌的同时保持电性能的发挥。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977463A_ABST
    Figure CN122977463A_ABST
Patent Text Reader

Abstract

The application discloses a ternary precursor, a preparation method thereof and a battery, and relates to the technical field of batteries.A plurality of primary particles with a ladder-type increasing L / d from inside to outside are constructed in the secondary particles of the ternary precursor: the innermost layer is a stress buffer zone, which inhibits the appearance of micro-cracks at the source and significantly reduces the particle cracking rate in the charging and discharging process; the middle layer ensures the rapid transmission of lithium ions in the deep material and effectively improves the discharge capacity of the positive electrode material; and the outermost layer is conducive to promoting ion transmission.The structure is beneficial to shortening the lithium ion diffusion path, improving the product capacity, and ensuring that both large and small particles can maintain macroscopic morphology while maintaining the play of electrical performance.The preparation method is prepared by ladder-type reduction of pH value, ladder-type increase of ammonia concentration and ladder-type reduction of rotating speed, and is multi-angle synergistically controlled, and the preparation process uses existing equipment, without additional equipment or raw materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically, to ternary precursors and their preparation methods, and batteries. Background Technology

[0002] In recent years, high-nickel and medium-nickel high-voltage nickel-cobalt-manganese ternary cathode materials have become a research hotspot in power batteries due to their high energy density. As precursors for cathode materials, the internal crystal structure and microstructure of the ternary precursor, including the morphology of secondary particles, the arrangement of primary particles, and the distribution of crystal defects, have a decisive influence on the electrochemical performance of the final cathode material.

[0003] In conventional coprecipitation crystallization reactions, process parameters are usually kept constant or exhibit a simple two-stage change (nucleation and growth), resulting in a generally uniform internal morphology of the prepared precursor particles. With the increasing demand for both high capacity and long cycle life in batteries, this conventional uniform structure has revealed serious limitations: First, for precursors of different particle sizes, if the primary particles are too densely packed, the solid-phase diffusion path of lithium ions is prolonged, preventing the effective release of deep active sites at high rates and significantly limiting discharge capacity. Second, ternary materials often experience severe anisotropic lattice strain during charging and discharging. Conventionally disordered or uniformly morphological primary particles are prone to stress concentration during stress transmission, leading to radial cracking within secondary particles. This accelerates electrolyte penetration, exacerbates transition metal dissolution, and ultimately results in rapid capacity decay and deterioration of cycle performance, triggering side reactions and causing a sharp collapse in capacity performance.

[0004] Existing technologies often employ homogenization control, failing to establish a correlation between macroscopic particle size and ion transport for particles of different sizes. Therefore, constructing multi-level morphology gradients for different particle sizes is one of the key technical bottlenecks that urgently needs to be addressed in the field of ternary precursors.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a ternary precursor and its preparation method, as well as a battery, to solve or improve the above-mentioned technical problems.

[0007] This invention is implemented as follows: In a first aspect, the present invention provides a ternary precursor, wherein the secondary particles of the ternary precursor are spherical and include multiple layers of primary particles that increase in size from the inside to the outside; the particle size D50 of the secondary particles is 2μm-20μm. The primary particles exhibit a nanosheet-like morphology with an aspect ratio L / d of 0.9-10; where L is the long axis diameter of the primary particle nanosheet, which is parallel to the nanosheet stacking orientation direction; and d is the short axis diameter of the primary particle nanosheet, which is perpendicular to the nanosheet stacking orientation direction.

[0008] In an optional implementation, when the particle size D50 of the secondary particles is 2μm-6μm, the number of layers of the primary particles is 3. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 35%), and its L / d is 0.9-1.5; The intermediate layer primary particles are located within a radius of (35%, 75%), with an L / d ratio of 2.0-3.5; The outermost primary particles are located within a radius of (75%, 100%), with an L / d of 4.0-5.5.

[0009] In an optional implementation, when the particle size D50 of the secondary particles is 6μm-12μm, the number of layers of the primary particles is 4. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 25%), and its L / d is 0.9-1.2; The first layer of particles in the middle is located within a radius of (25%, 55%), and its L / d is 1.8-3.0; The secondary particles in the middle layer are located within a radius of (55%, 85%), and their L / d ratio is 3.5-5.5. The outermost primary particles are located within a radius of (85%, 100%), with an L / d of 6.0-7.5.

[0010] In an optional implementation, when the particle size D50 of the secondary particles is 12μm-20μm, the number of layers of the primary particles is 5-6. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 20%), and its L / d is 0.9-1.1; Based on the innermost layer, the intermediate layers of primary particles are located within a radius of (20%, 80%), and their L / d increases outward in an arithmetic progression, with the arithmetic progression Δ(L / d) = 1.2-1.8. The outermost primary particles are located within a radius of (80%, 100%), and their L / d is 8.0-10.0.

[0011] In an optional implementation, the general formula of the ternary precursor is Ni. x Co y Mn (1-x-y)(OH)2, where 0.5 < x < 1, 0 < y < 0.3; tap density TD is 1.0-2.5; retention rate ≥ 90% after 100 cycles.

[0012] Secondly, the present invention provides a method for preparing a ternary precursor as described in any of the foregoing embodiments, comprising the following steps: A mixed salt solution, precipitant, and complexing agent were added to a reaction vessel to prepare a ternary precursor. During the reaction, a protective gas was continuously introduced, and the following operations were performed simultaneously: The pH value is reduced in a stepwise manner, with each stage reducing the pH value by 0.15-0.25 units compared to the previous stage; The ammonia concentration is increased in a stepwise manner, with the ammonia concentration in each stage increasing by 2g / L-4g / L compared to the previous stage; The engine speed is reduced in stages, with each stage reducing the speed by 50-100 rpm compared to the previous stage.

[0013] In an optional embodiment, during the preparation of the ternary precursor, the pH of the reaction system is controlled to be 9.5-12.5, the ammonia concentration to be 0.5 g / L-20 g / L, the temperature to be 40℃-80℃, and the rotation speed to be 100 rpm-1000 rpm.

[0014] In an optional embodiment, the concentration of the mixed salt solution is 1 mol / L-2.5 mol / L, the concentration of the precipitant is 8 mol / L-12 mol / L, and the concentration of the complexing agent is 5 mol / L-8 mol / L. And / or, the mixed salt is selected from nickel salts, cobalt salts, and manganese salts in a molar ratio of (6-9.9):(0.02-2.5):(0.01-3.5); wherein the nickel salt is selected from at least one of nickel sulfate, nickel nitrate, and nickel chloride; the cobalt salt is selected from at least one of cobalt sulfate, cobalt nitrate, and cobalt chloride; and the manganese salt is selected from at least one of manganese sulfate, manganese nitrate, and manganese chloride. And / or, the precipitant is selected from at least one of sodium hydroxide and sodium carbonate; And / or, the complexing agent is selected from at least one of ammonia, ammonium chloride, ammonium nitrate and citric acid.

[0015] In an optional embodiment, the preparation method further includes post-processing, which includes: The slurry obtained from the reaction system is placed in an aging container for aging treatment to obtain an aged product; The aged product is subjected to a first filtration process to obtain a first filter cake; an alkaline solution is added to the first filter cake for slurry treatment to obtain a slurry product; the concentration of the alkaline solution is 0.1 mol / L-10 mol / L, and the type of alkaline solution includes liquid alkali; The pulping product is subjected to a second filtration process to obtain a second filtered product. The second filtered product is dried, sieved, and demagnetized to obtain a ternary precursor.

[0016] Thirdly, the present invention provides a battery comprising a ternary precursor as described in any of the foregoing embodiments or a ternary precursor prepared by any of the foregoing embodiments.

[0017] The present invention has the following beneficial effects: The ternary precursor provided in this invention is a high-capacity ternary precursor. It achieves this by constructing a multi-layered morphological gradient structure within the secondary particles of the ternary precursor, with the L / d ratio increasing in a stepwise manner from the inside out. As the particle size of the secondary particles increases, the number of primary particle layers also increases. The innermost primary particles establish a stress buffer zone, suppressing the occurrence of microcracks at the source and significantly reducing the particle cracking rate during charging and discharging. The middle layer of primary particles ensures rapid lithium-ion transport within the deeper material, effectively improving the discharge capacity of the cathode material. The outermost primary particles promote ion transport. This invention, through its multi-level buffer structure, spontaneously forms high-porosity ion transport channels, greatly shortening the lithium-ion diffusion path and increasing product capacity. It ensures that regardless of particle size, both large and small particles maintain their macroscopic morphology while preserving their electrical performance.

[0018] For secondary particles of different sizes, by controlling the co-precipitation reaction, the pH value was decreased stepwise, the ammonia concentration was increased stepwise, and the rotation speed was decreased stepwise, achieving multi-faceted morphological gradient layers with a stepwise L / d distribution from the inside out. The preparation process can use existing equipment without introducing additional equipment or raw materials. Attached Figure Description

[0019] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 SEM images of the product obtained in Example 1; Figure 2 SEM images of the product obtained in Example 2; Figure 3 Here are SEM images of the product obtained in Example 3; Figure 4 Here are the SEM images of the products obtained in Comparative Example 1; Figure 5 The image shown is a SEM image of the product obtained in Comparative Example 2. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0022] In a first aspect, the present invention provides a ternary precursor, wherein the secondary particles of the ternary precursor are spherical and include multiple layers of primary particles that increase in size from the inside to the outside; the particle size D50 of the secondary particles is 2μm-20μm. The primary particles exhibit a nanosheet-like morphology with an aspect ratio L / d of 0.9-10; where L is the long axis diameter of the primary particle nanosheet, which is parallel to the nanosheet stacking orientation direction; and d is the short axis diameter of the primary particle nanosheet, which is perpendicular to the nanosheet stacking orientation direction.

[0023] This invention constructs a multi-level morphological gradient structure with a stepped L / d ratio inside the secondary particles of the ternary precursor. As the particle size of the secondary particles increases, the number of layers of the primary particles increases simultaneously, thereby establishing a stress buffer zone. Through multi-level buffering, highly porous ion transport channels are spontaneously formed, greatly shortening the lithium-ion diffusion path and improving product capacity. This ensures that both large and small particles maintain their macroscopic morphology while preserving their electrical performance.

[0024] The low L / d structure in the inner layer effectively counteracts the lattice stress propagating towards the center, thereby suppressing the occurrence of microcracks at the source and significantly reducing the particle cracking rate during charging and discharging. The analysis is as follows: Due to the constrained aspect ratio (L / d≤1.5), the innermost layer of the precursor secondary particles has a near-equiaxed blocky morphology, lacking preferred orientation among themselves. During subsequent sintering into the cathode material and lithium insertion / extraction / deintercalation, the material undergoes lattice contraction. At this time, the equiaxed blocky crystal in the innermost layer can weaken and absorb the stress propagating towards the center, eliminating stress concentration points and suppressing the occurrence of "inside-out" cracks in the secondary particles from the source, thus reducing the overall particle cracking rate during long-term cycling.

[0025] Meanwhile, the gradually increasing L / d ratio ensures the rapid transport of lithium ions in the deep material, effectively improving the discharge capacity of the cathode material.

[0026] The outermost layer, or surface layer, has a high L / d structure, which is conducive to promoting ion transport. The analysis is as follows: the outermost primary particles of the precursor have a relatively long diameter. These nanosheet-like primary particles with high aspect ratios are arranged radially in three-dimensional space, supporting each other in space and spontaneously forming radial channels with high porosity, which is more conducive to lithium ion transport and maximizes the capacity of the cathode material.

[0027] In an optional implementation, when the particle size D50 of the secondary particles is 2μm-6μm, the number of layers of the primary particles is 3. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 35%), and its L / d is 0.9-1.5; The intermediate layer primary particles are located within a radius of (35%, 75%), with an L / d ratio of 2.0-3.5; The outermost primary particles are located within a radius of (75%, 100%), with an L / d of 4.0-5.5.

[0028] For example, the innermost primary particle is located in a region with a radius of (0, 35%). "(" indicates that the corresponding endpoint value 0 is not included, and "]" indicates that the corresponding endpoint value 35% is included. Similar descriptions in the following text all mean the same thing and will not be repeated.

[0029] In an optional implementation, when the particle size D50 of the secondary particles is 6μm-12μm, the number of layers of the primary particles is 4. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 25%), and its L / d is 0.9-1.2; The first layer of particles in the middle is located within a radius of (25%, 55%), and its L / d is 1.8-3.0; The secondary particles in the middle layer are located within a radius of (55%, 85%), and their L / d ratio is 3.5-5.5. The outermost primary particles are located within a radius of (85%, 100%), with an L / d of 6.0-7.5.

[0030] In an optional implementation, when the particle size D50 of the secondary particles is 12μm-20μm, the number of layers of the primary particles is 5-6. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 20%), and its L / d is 0.9-1.1; Based on the innermost layer, the intermediate layers of primary particles are located within a radius of (20%, 80%), and their L / d increases outward in an arithmetic progression, with the arithmetic progression Δ(L / d) = 1.2-1.8. The outermost primary particles are located within a radius of (80%, 100%), and their L / d is 8.0-10.0.

[0031] In an optional implementation, the general formula of the ternary precursor is Ni. x Co y Mn(1-x-y) (OH)2, where 0.5 < x < 1, 0 < y < 0.3; tap density TD is 1.0-2.5; retention rate ≥ 90% after 100 cycles.

[0032] It should be noted that for ternary precursor materials of the same type, if the difference in 0.1C discharge capacity is greater than 2 mAh / g in electrical performance testing, the ternary precursor material can be considered to be of high capacity. The ternary precursor material provided by this invention is of high capacity.

[0033] Secondly, the present invention provides a method for preparing a ternary precursor as described in any of the foregoing embodiments, comprising the following steps: A mixed salt solution, precipitant, and complexing agent were added to a reaction vessel to prepare a ternary precursor. During the reaction, a protective gas was continuously introduced, and the following operations were performed simultaneously: The pH value is reduced in a stepwise manner, with each stage reducing the pH value by 0.15-0.25 units compared to the previous stage; The ammonia concentration is increased in a stepwise manner, with the ammonia concentration in each stage increasing by 2g / L-4g / L compared to the previous stage; The engine speed is reduced in stages, with each stage reducing the speed by 50-100 rpm compared to the previous stage.

[0034] The embodiments of the present invention do not impose any particular limitation on the type of protective gas, which can be selected according to actual needs, such as nitrogen, helium, etc.

[0035] This invention addresses secondary particles of different sizes by selectively setting 3-6 layers of morphological gradients with a stepped L / d distribution from the inside out through controlled co-precipitation reactions. The preparation process can utilize existing equipment without the need for additional equipment or raw materials.

[0036] Specifically, this invention synergistically regulates the precipitation rate of metal ions, the crystal growth of primary particles, and their stacking orientation by gradually reducing the pH value, increasing the ammonia concentration, and decreasing the rotation speed, thereby forming a multilayer structure with a stepwise increase in L / d from the inside out. In the initial stage of the reaction, a higher pH value, lower ammonia concentration, and higher rotation speed are used to accelerate the nucleation rate of the system and inhibit directional crystal growth through strong shearing action, resulting in low L / d, near-equiaxed primary particles. This structure, located within the secondary particles, can disperse lattice stress during charging and discharging, reducing central stress concentration and the risk of particle cracking.

[0037] As the particles grow, gradually decreasing the pH value, increasing the ammonia concentration, and reducing the rotation speed can slow down instantaneous precipitation and the formation of new crystal nuclei, promote the growth of primary particles along the dominant crystal orientation, and weaken shear fragmentation. This causes the outer primary particles to gradually form high L / d nanosheets and align radially. This creates pores and ion transport channels extending from the surface inwards, shortening the lithium-ion diffusion path and improving the utilization rate of internal active materials and discharge capacity. Simultaneously, the intermediate gradient layer can buffer structural changes and lattice stress, enabling the material to achieve both high capacity and good cycle stability.

[0038] In an optional embodiment, during the preparation of the ternary precursor, the pH of the reaction system is controlled to be 9.5-12.5, the ammonia concentration to be 0.5 g / L-20 g / L, the temperature to be 40℃-80℃, and the rotation speed to be 100 rpm-1000 rpm.

[0039] For example, taking a secondary particle size D50 of 2μm-6μm and a primary particle layer of 3 layers as an example, the process parameters are set as follows: If the innermost layer is prepared, the pH is 10.5, the ammonia concentration is 0.5g / L, and the rotation speed is 600rpm; in the subsequent preparation process, the pH decreases stepwise, and the pH for preparing the middle layer is 10.5-(0.15-0.25), the ammonia concentration is 0.5g / L+(2g / L-4g / L), and the rotation speed is 600rpm-(50rpm-100rpm).

[0040] In an optional embodiment, the concentration of the mixed salt solution is 1 mol / L-2.5 mol / L, the concentration of the precipitant is 8 mol / L-12 mol / L, and the concentration of the complexing agent is 5 mol / L-8 mol / L; the concentration of the substances can be reasonably set according to actual needs.

[0041] For example, the concentration of the mixed salt solution can be selected from any one of 1 mol / L, 1.3 mol / L, 1.6 mol / L, 1.8 mol / L, 2 mol / L, and 2.5 mol / L, or other values ​​within the range of 1 mol / L to 2.5 mol / L. The concentration of the precipitant can be selected from any one of 8 mol / L, 8.5 mol / L, 9 mol / L, 9.5 mol / L, 10 mol / L, 11 mol / L, and 12 mol / L, or other values ​​within the range of 8 mol / L to 12 mol / L. The concentration of the complexing agent can be selected from any one of 5 mol / L, 5.5 mol / L, 6 mol / L, 6.5 mol / L, 7 mol / L, 7.5 mol / L, and 8 mol / L, or other values ​​within the range of 5 mol / L to 8 mol / L.

[0042] And / or, the mixed salt is selected from nickel salts, cobalt salts and manganese salts in a molar ratio of (6-9.9):(0.02-2.5):(0.01-3.5); wherein the nickel salt is selected from at least one of nickel sulfate, nickel nitrate and nickel chloride; the cobalt salt is selected from at least one of cobalt sulfate, cobalt nitrate and cobalt chloride; and the manganese salt is selected from at least one of manganese sulfate, manganese nitrate and manganese chloride.

[0043] For example, the molar ratio of nickel, cobalt, and manganese salts can be selected from 8:1:1, 6:2:2, etc. When the molar ratio of nickel, cobalt, and manganese salts is 8:1:1, the molar proportion of nickel in the mixed salt is 80%, abbreviated as NCM811, which belongs to high-nickel materials; when the molar ratio of nickel, cobalt, and manganese salts is 6:2:2, the molar proportion of nickel in the mixed salt is 60%, abbreviated as NCM622, which belongs to medium-nickel materials. The molar ratio of nickel, cobalt, and manganese salts can be reasonably selected according to actual needs. In addition, when the molar content of nickel satisfies the following relationship, 60% ≤ nickel content < 70%, the corresponding product is called a 6-series product.

[0044] In the preferred embodiment of the present invention, nickel salts, cobalt salts, and manganese salts are selected as their respective sulfates (NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O); in other embodiments of the present invention, other types may be selected as needed.

[0045] And / or, the precipitant is selected from at least one of sodium hydroxide and sodium carbonate; the precipitant mainly reacts with dissolved metal ions (such as Ni, Co and Mn) to form precursor precipitates.

[0046] In the optimal implementation, sodium hydroxide is used as the precipitant. The corresponding hydroxide precursor decomposes more thoroughly during subsequent calcination, making it easier to form a dense, highly crystalline cathode material, which is beneficial for achieving high capacity.

[0047] And / or, the complexing agent is selected from at least one of ammonia, ammonium chloride, ammonium nitrate, and citric acid. The core function of the complexing agent is to complex free metal ions in the reaction vessel, reduce their supersaturation, and thus precisely control the nucleation and growth rate of the product to obtain secondary particles with high sphericity, uniform particle size, and high tap density.

[0048] In the optimal implementation, ammonia is used as the complexing agent. Ammonia has a moderate complexing constant, which can be easily controlled precisely by pH value and ammonia concentration. It is also easy to remove in subsequent washing processes with little residue.

[0049] In an optional embodiment, the preparation method further includes post-processing, which includes: The slurry obtained from the reaction system is placed in an aging container for aging treatment to obtain an aged product; The aged product is subjected to a first filtration process to obtain a first filter cake; an alkaline solution is added to the first filter cake for slurry treatment to obtain a slurry product; the concentration of the alkaline solution is 0.1 mol / L-10 mol / L, and the type of alkaline solution includes liquid alkali; The pulping product is subjected to a second filtration process to obtain a second filtered product. The second filtered product is dried, sieved, and demagnetized to obtain a ternary precursor.

[0050] At the end of the reaction, the newly formed precipitate particles have low crystallinity and lattice defects. During aging, the smaller particles, due to their higher solubility, dissolve and redeposit on the surface of the larger particles, resulting in a more complete crystal structure, reduced defects, and improved particle size uniformity. Furthermore, it provides time for impurity ions (such as sulfate and sodium ions) encapsulated within the secondary particles to diffuse into the solution, thus achieving preliminary purification. It also facilitates the transformation of unstable amorphous or transitional phases into stable target crystal forms.

[0051] Specifically, in the embodiments of the present invention, the aging process involves allowing the slurry produced from the reaction vessel to stand still, and then separating the solid and liquid components for easy filtration.

[0052] The first filtration process separates the solid precursor from the mother liquor, which contains a large amount of unreacted metal ions, sulfate ions, and fine powder. The separated mother liquor can be recycled. This operation facilitates the subsequent slurry treatment to efficiently remove impurities remaining on the particle surface.

[0053] Slurry treatment ensures that the alkaline solution can fully contact the surface of all particles, guaranteeing a uniform washing effect. It is beneficial for deep cleaning of unreacted metal ions and sulfate ions in the product. Using alkaline solution helps unreacted ions form soluble salts, which can be completely separated in subsequent filtration, reducing the impurity content of the product to an extremely low level. This is beneficial for improving the reactivity during subsequent mixing and sintering with the lithium source.

[0054] The second filtration process is the final step to remove the liquid between the particles, resulting in a pure wet material containing only the particles themselves and a small amount of surface moisture, which is then prepared for drying.

[0055] The drying process evaporates the physically adsorbed water between and inside the particles, preventing the wet material from clumping during storage and affecting its performance; the resulting dry powder is convenient for subsequent processing and storage.

[0056] Screening removes hard agglomerates or large particles that may form during the drying process or accidentally introduce coarse impurities, ensuring particle size consistency and that the particle size distribution meets specifications, thus avoiding uneven local reactions caused by large particles during subsequent sintering.

[0057] During the production process (equipment wear, raw material contamination, etc.), trace amounts of elemental iron, stainless steel fragments, and other magnetic materials inevitably get mixed in. These magnetic metal particles remain in the positive electrode material and, after the battery is made, may puncture the separator, causing an internal short circuit and triggering thermal runaway (fire, explosion). Demagnetization treatment helps ensure battery safety.

[0058] In summary, the preparation method of the ternary precursor includes the following steps: (1) Raw material preparation The general formula for ternary precursors is Ni x Co y Mn (1-x-y) (OH)2, where 0.5 < x < 1, 0 < y < 0.3. The concentration of the mixed salt solution is 1 mol / L-2.5 mol / L. The mixed salts are selected from nickel, cobalt, and manganese salts with a molar ratio of 8:1:1 or 6:2:2. The nickel, cobalt, and manganese salts are all sulfates (NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O).

[0059] The concentration of the precipitant is 8 mol / L-12 mol / L, and the precipitant is sodium hydroxide.

[0060] The concentration of the complexing agent is 5 mol / L-8 mol / L, and the complexing agent is ammonia.

[0061] (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) are added to the reaction vessel for reaction. During the reaction, a protective gas is continuously introduced, and the following operations are performed simultaneously: The pH value is reduced in a stepwise manner, with each stage reducing the pH value by 0.15-0.25 units compared to the previous stage; The ammonia concentration is increased in a stepwise manner, with the ammonia concentration in each stage increasing by 2g / L-4g / L compared to the previous stage; The engine speed is reduced in stages, with each stage reducing the speed by 50-100 rpm compared to the previous stage.

[0062] (3) Post-processing After the coprecipitation reaction is completed, the slurry obtained from the reaction system in step (2) is placed in an aging container for aging treatment to obtain the aged product; The aged product is subjected to a first filtration process to obtain a first filter cake; an alkaline solution is added to the first filter cake for slurry treatment to obtain a slurry product; the concentration of the alkaline solution is 0.1 mol / L-10 mol / L, and the type of alkaline solution includes liquid alkali; The pulping product is subjected to a second filtration process to obtain a second filtered product. The second filtered product is dried, sieved, and demagnetized to obtain a ternary precursor.

[0063] The prepared ternary precursor was tested. The particle size D50 of the secondary particles of the ternary precursor was 2μm-20μm; the secondary particles were spherical and consisted of 3-6 layers of primary particles with a stepped increase from the inside out; the tap density TD of the secondary particles was 1.0-2.5; and the retention rate after 100 cycles was ≥90%. Among them, the primary particles had a nanosheet morphology with an aspect ratio L / d of 0.9-10; where L is the long axis diameter of the primary particle nanosheet, which is parallel to the nanosheet stacking orientation direction; and d is the short axis diameter of the primary particle nanosheet, which is perpendicular to the nanosheet stacking orientation direction.

[0064] Thirdly, the present invention provides a battery comprising a ternary precursor as described in any of the foregoing embodiments or a ternary precursor prepared by any of the foregoing embodiments.

[0065] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0066] Example 1 This embodiment provides a ternary precursor, the preparation method of which includes the following steps: (1) Raw material preparation The precursor is composed of Ni 0.8 Co 0.1 Mn 0.1 (OH)2, abbreviated as NCM811; target D50=4μm, set 3 L / d topography gradient layers.

[0067] A mixed metal salt solution was prepared using NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O as raw materials, with a molar ratio of Ni:Co:Mn = 8:1:1, and a total metal ion concentration of 2.0 mol / L. A 10 mol / L NaOH solution was used as the precipitant, and a 6 mol / L ammonia solution was used as the complexing agent.

[0068] (2) Coprecipitation reaction The mixed salt solution, NaOH solution, and ammonia water prepared in step (1) are simultaneously and continuously pumped into the reactor. Nitrogen gas is introduced as a protective gas throughout the process, and the following operations are performed simultaneously: In the innermost layer (first layer), during the nucleation stage: the system pH was controlled at 11.80 ± 0.05, ammonia concentration at 3.0 g / L, rotation speed at 600 rpm, and temperature at 55℃. Under the synergistic effect of low supersaturation and weak complexation, the primary particles formed a near-equiaxed blocky morphology with no obvious preferred orientation. The L / d ratio of this layer was controlled within the range of 0.9-1.5, corresponding to the cross-section of the secondary particles located in the radius region of (0, 35%).

[0069] Intermediate layer (second layer), growth stage: Adjust the system to pH = 11.60 ± 0.05 (0.20 units lower than the first layer stage), ammonia concentration = 3.5 g / L (0.5 g / L higher than the first layer stage), rotation speed 590 rpm (10 rpm lower than the first layer stage), and maintain temperature at 55℃. The increased ammonia concentration enhances the metal ion complexation ability. Combined with the directional control of pH, this promotes preferential growth of primary particles along their long axis, increasing L / d to 2.0-3.5. The orientation gradually transitions from random to radial, corresponding to the secondary particles' cross-section located in the (35%, 75%) radius region.

[0070] The third layer, the growth stage: The system was adjusted to pH = 11.40 ± 0.05 (0.20 units lower than the second layer), ammonia concentration = 7.0 g / L (3.5 g / L higher than the second layer), rotation speed 530 rpm (60 rpm lower than the second layer), and temperature maintained at 55℃. The aspect ratio of the primary particles increased significantly, reaching 4.0-5.5 L / d, exhibiting a radially divergent arrangement of high aspect ratio nanosheets, with spontaneously formed radial open pore channels between the sheets. The corresponding cross-section of the secondary particles was located in the [75%, 100% radius region].

[0071] (3) Post-processing After the coprecipitation reaction is completed, the slurry obtained from the reaction system in step (2) is placed in an aging container for aging treatment to obtain the aged product; The aged product is subjected to a first filtration process to obtain a first filter cake; an alkaline solution is added to the first filter cake for slurry treatment to obtain a slurry product; the concentration of the alkaline solution is 3 mol / L, and the type of alkaline solution is liquid alkali; The pulping product is subjected to a second filtration process to obtain a second filtered product. The second filtered product is dried, sieved, and demagnetized to obtain a ternary precursor.

[0072] The obtained ternary precursor secondary particles were found to be spherical with a particle size D50 of 4.18 μm, and the L / d ratios of the first layer, the second layer, and the third layer were 1.12, 2.68, and 4.75, respectively.

[0073] Example 2 This embodiment provides a ternary precursor, the preparation method of which includes the following steps: (1) Raw material preparation Precursor composition: Ni 0.6 Co 0.2 Mn 0.2 (OH)2, abbreviated as NCM622; target D50=9μm, 4 L / d morphology gradient layers are set.

[0074] A mixed metal salt solution was prepared using NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O as raw materials, with a total metal ion concentration of 2.0 mol / L, according to the molar ratio of Ni:Co:Mn = 6:2:2. A 10 mol / L NaOH solution was used as the precipitant and a 6 mol / L ammonia solution was used as the complexing agent.

[0075] (2) Coprecipitation reaction The mixed salt solution, NaOH solution, and ammonia water prepared in step (1) are simultaneously and continuously pumped into the reactor. Nitrogen gas is introduced as a protective gas throughout the process, and the following operations are performed simultaneously: Innermost layer (first layer), nucleation stage: The system was adjusted to pH = 11.80 ± 0.05, ammonia concentration = 4.0 g / L, rotation speed 550 rpm, and temperature 60℃. Primary particles grew into equiaxed microcrystalline morphology under near-supersaturated conditions of high pH and low ammonia concentration, with L / d controlled within the range of 0.9-1.2. The corresponding cross-section of the secondary particles was located in the radius region of (0, 25%).

[0076] The first (second) intermediate layer, growth stage: The system was adjusted to pH = 11.60 ± 0.05 (0.20 units lower than the first layer stage), ammonia concentration = 4.5 g / L (0.5 g / L higher than the first layer stage), rotation speed 530 rpm (20 rpm lower than the first layer stage), and temperature 60℃. The long axis growth of the primary particles accelerated, with L / d increasing to 1.8~3.0, corresponding to the cross-section of the secondary particles located in the (25%, 55%) radius region.

[0077] The second (third) intermediate layer, growth stage: adjust the system to pH = 11.40 ± 0.05 (0.20 units lower than the second layer stage), ammonia concentration = 8.0 g / L (3.5 g / L higher than the second layer stage), rotation speed 470 rpm (60 rpm lower than the second layer stage), temperature 60℃. As L / d increases to 3.5-5.5, radial orientation gradually strengthens, corresponding to the secondary particle cross-section located in the (55%, 85%) radius region.

[0078] The outermost layer (fourth layer), growth stage: The system was adjusted to pH = 11.20 ± 0.05 (0.20 units lower than the third layer stage), ammonia concentration = 11.5 g / L (3.5 g / L higher than the third layer stage), rotation speed 405 rpm (65 rpm lower than the third layer stage), and temperature 60℃. The primary particles formed ultra-long nanosheet morphology with L / d reaching 6.0-7.5, radially neatly arranged, forming highly porous channels, corresponding to the cross-section of the secondary particles located in the [85%, 100% radius region].

[0079] (3) Post-processing The implementation steps of this process are the same as the post-processing (3) corresponding to Example 1.

[0080] The obtained ternary precursor secondary particles were found to be spherical with a particle size D50 of 9.23 μm. The L / d ratios were 1.08 for the first layer, 2.45 for the second layer, 4.62 for the third layer, and 7.05 for the fourth layer.

[0081] Example 3 This embodiment provides a ternary precursor, the preparation method of which includes the following steps: (1) Raw material preparation Precursor composition: Ni 0.8 Co 0.1 Mn 0.1 (OH)2, abbreviated as NCM811; target D50=15μm, set 5 L / d topographic gradient layers, with the innermost layer as the base, and the L / d of each layer increasing towards the outer layer in an arithmetic progression of Δ(L / d)=1.75.

[0082] A mixed metal salt solution was prepared using NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O as raw materials, with a molar ratio of Ni:Co:Mn = 8:1:1, and a total metal ion concentration of 2.0 mol / L. A 10 mol / L NaOH solution was used as the precipitant, and a 6 mol / L ammonia solution was used as the complexing agent.

[0083] (2) Coprecipitation reaction The mixed salt solution, NaOH solution, and ammonia water prepared in step (1) are simultaneously and continuously pumped into the reactor. Nitrogen gas is introduced as a protective gas throughout the process, and the following operations are performed simultaneously: Innermost layer (first layer), nucleation stage: control system pH=11.80±0.05, ammonia concentration=3.5g / L, rotation speed 560rpm, temperature 55℃. Primary particles form microcrystalline equiaxed morphology with L / d=0.9-1.1, corresponding to the cross-section of secondary particles located in the radius region of (0, 20%).

[0084] The first (second) intermediate layer, growth stage: The system was adjusted to pH = 11.60 ± 0.05 (0.20 units lower than the first layer stage), ammonia concentration = 4.0 g / L (0.5 g / L higher than the first layer stage), rotation speed 540 rpm (20 rpm lower than the first layer stage), and temperature 55℃. The primary particle size (L / d) increased to approximately 2.75, Δ(L / d) = 1.75, corresponding to the secondary particle cross-section located in the (20%, 40%) radius region.

[0085] The second (third) intermediate layer, growth stage: The system was adjusted to pH = 11.40 ± 0.05 (0.20 units lower than the second layer stage), ammonia concentration = 6.5 g / L (2.5 g / L higher than the second layer stage), rotation speed 480 rpm (60 rpm lower than the second layer stage), and temperature 55℃. The primary particle size (L / d) increased to approximately 4.5, Δ(L / d) = 1.75, corresponding to the secondary particle cross-section located in the (40%, 60%) radius region.

[0086] The third (fourth) intermediate layer, growth stage: The system was adjusted to pH = 11.20 ± 0.05 (0.20 units lower than the third layer stage), ammonia concentration = 9.5 g / L (3.0 g / L higher than the third layer stage), rotation speed 415 rpm (65 rpm lower than the third layer stage), and temperature 55℃. The primary particle size (L / d) increased to approximately 6.25, Δ(L / d) = 1.75, corresponding to the secondary particle cross-section located in the (60%, 80%) radius region.

[0087] Fifth layer, growth stage: The system was adjusted to pH = 11.0 ± 0.05 (0.20 units lower than the fourth layer), ammonia concentration = 13.0 g / L (3.5 g / L higher than the fourth layer), rotation speed 348 rpm (67 rpm lower than the fourth layer), and temperature 55℃. The primary particle L / d reached approximately 8.0, Δ(L / d) = 1.75, forming a radially arranged, ultra-high aspect ratio plate-like structure, corresponding to the secondary particle cross-section located in the [80%, 100%] radius region.

[0088] (3) Post-processing The implementation steps of this process are the same as the post-processing (3) corresponding to Example 1.

[0089] The obtained ternary precursor secondary particles were found to be spherical with a particle size D50 of 15.32 μm. The L / d ratios were as follows: first layer = 1.02, second layer = 2.73, third layer = 4.48, fourth layer = 6.21, and fifth layer = 8.05.

[0090] Comparative Example 1 This comparative example provides a ternary precursor, the preparation method of which is the same as that of Example 1, except that it includes the following steps: (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) are simultaneously pumped into the reactor. Nitrogen gas is purged throughout the process as a protective gas. The process conditions are kept constant throughout the process, and the pH is not decreased or the ammonia concentration is not increased stepwise. The process and parameters during the reaction are as follows: Maintain pH=11.60±0.05, ammonia concentration=3.5g / L, temperature 55℃, and rotation speed 590rpm, and continue the reaction until completion.

[0091] Testing revealed that the prepared ternary precursor particles exhibited uniform morphology and no gradient structure. The particle size D50 was 4.05 μm, and the L / d ratio was 1.5–2.5, with no gradient distribution from the inside out.

[0092] Comparative Example 2 This comparative example provides a ternary precursor, whose preparation method is the same as that of Example 2, except that it includes the following steps: (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) are simultaneously pumped into the reactor. Nitrogen gas is purged throughout the process as a protective gas. The process conditions are kept constant throughout the process, and the pH is not decreased or the ammonia concentration is not increased stepwise. The process and parameters during the reaction are as follows: Maintain pH=11.60±0.05, ammonia concentration=4.5g / L, temperature 60℃, and rotation speed 530rpm, and continue the reaction until completion.

[0093] Testing revealed that the prepared ternary precursor particles exhibited uniform morphology and no gradient structure. The particle size D50 was 9.01 μm, and the L / d ratio was 2.0–3.5, showing no gradient distribution from the inside out.

[0094] Comparative Example 3 This comparative example provides a ternary precursor, whose preparation method is the same as that of Example 3, except that it includes the following steps: (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) are simultaneously pumped into the reactor. Nitrogen gas is purged throughout the process as a protective gas. The process conditions are kept constant throughout the process, and the pH is not decreased or the ammonia concentration is not increased stepwise. The process and parameters during the reaction are as follows: Maintain pH=11.60±0.05, ammonia concentration=4.0g / L, temperature 55℃, and rotation speed 540rpm, and continue the reaction until completion.

[0095] Testing revealed that the prepared ternary precursor particles exhibited uniform morphology and no gradient structure. The particle size D50 was 14.8 μm, and the L / d ratio was 2.0-3.0, with no gradient distribution from the inside out.

[0096] Comparative Example 4 This comparative example provides a ternary precursor, whose preparation method is the same as that of Example 2, except that it includes the following steps: (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) are simultaneously pumped into the reactor. Nitrogen gas is introduced as a protective gas throughout the process. The process conditions are kept constant throughout the process. Only the pH is decreased stepwise, and the ammonia concentration is not increased stepwise or the rotation speed is not adjusted stepwise. The process and parameters during the reaction are as follows: Innermost layer (first layer), nucleation stage: Adjust the system to pH=11.80±0.05, ammonia concentration=4.5g / L, temperature 60℃, and rotation speed 530rpm; The first (second) intermediate layer, growth stage: adjust the system to pH=11.60±0.05 (0.20 units lower than the first layer stage), ammonia concentration=4.5g / L, temperature 60℃, rotation speed 530rpm; Second (third) layer in the middle, growth stage: adjust the system to pH=11.40±0.05 (0.20 units lower than the second layer stage), ammonia concentration=4.5g / L, temperature 60℃, rotation speed 530rpm; The outermost layer (fourth layer), growth stage: adjust the system to pH=11.20±0.05 (0.20 units lower than the third layer stage), ammonia concentration=4.5g / L, temperature 60℃, rotation speed 530rpm.

[0097] Testing revealed that the prepared ternary precursor particles exhibited uniform morphology and no gradient structure. The particle size D50 was 9.18 μm, and the L / d ratio was 2.5-2.8, showing no gradient distribution from the inside out.

[0098] Comparative Example 5 This comparative example provides a ternary precursor, whose preparation method is the same as that of Example 2, except that it includes the following steps: (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) are simultaneously pumped into the reactor. Nitrogen gas is introduced as a protective gas throughout the process. The process conditions are kept constant throughout the process, and the pH is decreased stepwise and the ammonia concentration is increased stepwise. The rotation speed is kept constant. The process and parameters during the reaction are as follows: Innermost layer (first layer), nucleation stage: Adjust the system to pH=11.80±0.05, ammonia concentration=4.0g / L, temperature 60℃, and rotation speed 530rpm; The first (second) intermediate layer, growth stage: adjust the system to pH=11.60±0.05 (0.20 units lower than the first layer stage), ammonia concentration=4.5g / L (0.5g / L higher than the first layer stage), temperature 60℃, rotation speed 530rpm; Second (third) layer in the middle, growth stage: adjust the system to pH=11.40±0.05 (0.20 units lower than the second layer stage), ammonia concentration=8.0g / L (3.5g / L higher than the second layer stage), temperature 60℃, rotation speed 530rpm; The outermost layer (fourth layer), growth stage: adjust the system to pH=11.20±0.05 (0.20 units lower than the third layer stage), ammonia concentration=11.5g / L (3.5g / L higher than the third layer stage), temperature 60℃, rotation speed 530rpm.

[0099] Testing revealed that the prepared ternary precursor particles exhibited uniform morphology and no gradient structure. The particle size D50 was 9.26 μm, and the L / d ratio ranged from 2.6 to 4.1, showing no gradient distribution from the inside out.

[0100] Comparative Example 6 This comparative example provides a ternary precursor, whose preparation method is the same as that of Example 2, except that it includes the following steps: (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) are simultaneously pumped into the reactor. Nitrogen gas is introduced as a protective gas throughout the process. The process conditions are kept constant throughout the process, and only the pH is decreased stepwise and the rotation speed is decreased gradient. The ammonia concentration is not increased stepwise. The process and parameters during the reaction are as follows: Innermost layer (first layer), nucleation stage: Adjust the system to pH=11.80±0.05, ammonia concentration=4.6g / L, rotation speed 550rpm, temperature 60℃.

[0101] Intermediate first layer (second layer), growth stage: adjust the system to pH=11.60±0.05 (0.20 units lower than the first layer stage), ammonia concentration=4.6g / L, rotation speed 530rpm (20rpm lower than the first layer stage), temperature 60℃.

[0102] Second (third) layer in the middle, growth stage: adjust the system to pH=11.40±0.05 (0.20 units lower than the second layer stage), ammonia concentration=4.6g / L, rotation speed 470rpm (60rpm lower than the second layer stage), temperature 60℃.

[0103] Outermost layer (fourth layer), growth stage: Adjust the system to pH=11.20±0.05 (0.20 units lower than the third layer stage), ammonia concentration=4.6g / L, rotation speed 405rpm (65rpm lower than the third layer stage), temperature 60℃.

[0104] Testing revealed that the prepared ternary precursor particles exhibited uniform morphology and no gradient structure. The particle size D50 was 9.26 μm, and the L / d ratio was 2.2–2.8, showing no gradient distribution from the inside out.

[0105] Comparative Example 7 This comparative example provides a ternary precursor, whose preparation method is the same as that of Example 2, except that it includes the following steps: (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) were simultaneously pumped into the reactor. Nitrogen gas was introduced as a protective gas throughout the process, and the process conditions were kept constant. The pH was increased stepwise, and the ammonia concentration and rotation speed gradient were adjusted to be consistent with those in Example 2. The process and parameters during the reaction were as follows: Innermost layer (first layer), nucleation stage: Adjust the system to pH=11.80±0.05, ammonia concentration=4.0g / L, rotation speed 550rpm, temperature 60℃.

[0106] Intermediate first layer (second layer), growth stage: adjust the system to pH=12.00±0.05 (0.20 units higher than the first layer stage), ammonia concentration=4.5g / L (0.5g / L higher than the first layer stage), rotation speed 530rpm (20rpm lower than the first layer stage), temperature 60℃.

[0107] At this stage, increasing the pH prevents the particle size from increasing, making it impossible to produce a qualified product, and the reaction terminates.

[0108] Comparative Example 8 This comparative example provides a ternary precursor, whose preparation method is the same as that of Example 2, except that it includes the following steps: (2) Coprecipitation reaction The mixed salt solution, precipitant, and complexing agent prepared in step (1) were simultaneously pumped into the reactor. Nitrogen gas was introduced as a protective gas throughout the process. The process conditions were kept constant throughout the process. The ammonia concentration was decreased stepwise. The pH control and rotation speed gradient adjustment were kept consistent with those in Example 2. The process and parameters during the reaction were as follows: Innermost layer (first layer), nucleation stage: Adjust the system to pH=11.80±0.05, ammonia concentration=4.0g / L, rotation speed 550rpm, temperature 60℃.

[0109] Intermediate first layer (second layer), growth stage: adjust the system to pH=11.60±0.05 (0.20 units lower than the first layer stage), ammonia concentration=3.0g / L (1.0g / L lower than the first layer stage), rotation speed 530rpm (20rpm lower than the first layer stage), temperature 60℃.

[0110] Second (third) layer in the middle, growth stage: adjust the system to pH=11.40±0.05 (0.20 units lower than the second layer stage), ammonia concentration=8.0g / L (1.0g / L lower than the second layer stage), rotation speed 470rpm (60rpm lower than the second layer stage), temperature 60℃.

[0111] After reducing the ammonia concentration at this stage, the reaction system produces micro-powder, resulting in stratification of the particle morphology and making it impossible to produce a qualified product, thus terminating the reaction.

[0112] Test Example 1 This test case performed SEM morphology analysis on the ternary precursors prepared in Examples 1-3 and Comparative Examples 1-2, and tested the cross-sectional images. Related images can be found in [link to relevant images]. Figures 1-5 : Figure 1 Example 1, Figure 2 Example 2, Figure 3 Example 3, Figure 4 For Comparative Example 1, Figure 5 For Comparative Example 2, the number of gradient layers of the ternary precursors obtained in Examples 1-3 was summarized, and the relevant results are shown in Table 1.

[0113] from Figure 1-5 It can be seen that, Figure 1 During the product preparation process, pH, ammonia concentration, and rotation speed are adjusted simultaneously. The small particle product is set with 3 L / d gradient layers, and the gradient range is controlled within the design range. The particles are slender and have obvious pores.

[0114] Figure 2 During the preparation process, pH, ammonia concentration, and rotation speed are adjusted simultaneously. The medium-particle product is set with 4 L / d gradient layers, and the gradient range is controlled within the design range. The L / d of the primary particles is higher than that of the traditional 6-series preparation method, and it has obvious porosity.

[0115] Figure 3 During the product preparation process, pH, ammonia concentration, and rotation speed are adjusted simultaneously. For large particle products, a gradient of 5 layers per L / d is set, and the gradient range is controlled within the design range. The particles are slender and have obvious pores.

[0116] Figure 4 During the preparation of the product, pH, ammonia concentration and rotation speed were not adjusted simultaneously. The process parameters were fixed throughout the process, no gradient layer was formed, the L / d data of the inner and outer layers did not change gradient, and the short axis diameter of the primary nanosheets increased.

[0117] Figure 5 During the preparation of the product, the pH, ammonia concentration, and rotation speed were not adjusted according to the patented method. The process parameters were fixed throughout the process, no gradient layer was formed, the L / d data of the inner and outer layers did not change gradient, and the short axis diameter of the primary nanosheets became thicker.

[0118] Test Example 2 This test example performs electrical performance tests on the ternary precursors prepared in Examples 1-3 and Comparative Examples 1-6.

[0119] The process of preparing ternary cathode material from ternary precursors is as follows: ternary precursors NCM811 and NCM622 are mixed with lithium hydroxide at a molar ratio of 1:1.05. The NCM811 mixture is sintered at 700℃, and the NCM622 mixture is sintered at 920℃. After being removed, ground and pulverized, the cathode material is finally obtained.

[0120] The process of assembling ternary cathode materials into coin cells is as follows: Cathode materials, conductive carbon, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 90:5:5 to form a slurry, which is then used to create the cathode electrode. A lithium metal sheet is used as the anode electrode, and the cells are assembled into coin cells. The coin cells are then subjected to electrochemical performance testing at 1C and 3.0V~4.35V.

[0121] The tap density, 0.1C discharge capacity, and 100-cycle retention rate of the ternary precursors obtained in Examples 1-3 and Comparative Examples 1-6 were summarized, and the relevant test results are shown in Table 1.

[0122] Table 1 Test Results

[0123] As can be seen from the data in Table 1, the products of Examples 1-3 prepared using the method of this application all have higher 0.1C discharge capacities than the corresponding comparative examples 1-6, indicating that the preparation method of this application has good applicability to ternary precursors with different particle sizes and nickel contents. By gradient control of the L / d ratio of the primary particles of the precursor, the lithium-ion transport performance and active material utilization of the material can be effectively improved, thereby increasing the discharge capacity of the cathode material and demonstrating a relatively stable and significant capacity improvement effect.

[0124] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A ternary precursor, characterized in that, The secondary particles of the ternary precursor are spherical and consist of multiple layers of primary particles that increase in size from the inside out; the particle size D50 of the secondary particles is 2μm-20μm. The primary particles have a nanosheet-like morphology with an aspect ratio L / d of 0.9-10; where L is the long axis diameter of the primary particle nanosheet, which is parallel to the nanosheet stacking orientation direction; and d is the short axis diameter of the primary particle nanosheet, which is perpendicular to the nanosheet stacking orientation direction.

2. The ternary precursor according to claim 1, characterized in that, When the particle size D50 of the secondary particles is 2μm-6μm, the number of layers of the primary particles is 3. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 35%), and its L / d is 0.9-1.5; The intermediate layer primary particles are located within a radius of (35%, 75%), with an L / d ratio of 2.0-3.5; The outermost primary particles are located within a radius of (75%, 100%), with an L / d of 4.0-5.

5.

3. The ternary precursor according to claim 1, characterized in that, When the particle size D50 of the secondary particles is 6μm-12μm, the number of layers of the primary particles is 4. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 25%), and its L / d is 0.9-1.2; The first layer of particles in the middle is located within a radius of (25%, 55%), and its L / d is 1.8-3.0; The secondary particles in the middle layer are located within a radius of (55%, 85%), and their L / d ratio is 3.5-5.

5. The outermost primary particles are located within a radius of (85%, 100%), with an L / d of 6.0-7.

5.

4. The ternary precursor according to claim 1, characterized in that, When the particle size D50 of the secondary particles is 12μm-20μm, the number of layers of the primary particles is 5-6. Among them, taking the center of the secondary particle as the starting point, the innermost primary particle is located in the region of radius (0, 20%), and its L / d is 0.9-1.1; Based on the innermost layer, the intermediate layers of primary particles are located within a radius of (20%, 80%), and their L / d increases outward in an arithmetic progression, with the arithmetic progression Δ(L / d) = 1.2-1.

8. The outermost primary particles are located within a radius of (80%, 100%), and their L / d is 8.0-10.

0.

5. The ternary precursor according to claim 1, characterized in that, The general formula of the ternary precursor is Ni x Co y Mn (1-x-y) (OH)2, where 0.5 < x < 1, 0 < y < 0.3; tap density TD is 1.0-2.5; retention rate ≥ 90% after 100 cycles.

6. A method for preparing a ternary precursor as described in any one of claims 1-5, characterized in that, Includes the following steps: A mixed salt solution, precipitant, and complexing agent were added to a reaction vessel to prepare a ternary precursor. During the reaction, a protective gas was continuously introduced, and the following operations were performed simultaneously: The pH value is reduced in a stepwise manner, with each stage reducing the pH value by 0.15-0.25 units compared to the previous stage; The ammonia concentration is increased in a stepwise manner, with the ammonia concentration in each stage increasing by 2g / L-4g / L compared to the previous stage; The engine speed is reduced in stages, with each stage reducing the speed by 50-100 rpm compared to the previous stage.

7. The preparation method according to claim 6, characterized in that, During the preparation of the ternary precursor, the pH of the reaction system was controlled at 9.5-12.5, the ammonia concentration at 0.5 g / L-20 g / L, the temperature at 40℃-80℃, and the rotation speed at 100 rpm-1000 rpm.

8. The preparation method according to claim 6, characterized in that, The concentration of the mixed salt solution is 1 mol / L-2.5 mol / L, the concentration of the precipitant is 8 mol / L-12 mol / L, and the concentration of the complexing agent is 5 mol / L-8 mol / L. And / or, the mixed salt is selected from nickel salts, cobalt salts, and manganese salts in a molar ratio of (6-9.9):(0.02-2.5):(0.01-3.5); wherein the nickel salt is selected from at least one of nickel sulfate, nickel nitrate, and nickel chloride; the cobalt salt is selected from at least one of cobalt sulfate, cobalt nitrate, and cobalt chloride; and the manganese salt is selected from at least one of manganese sulfate, manganese nitrate, and manganese chloride. And / or, the precipitant is selected from at least one of sodium hydroxide and sodium carbonate; And / or, the complexing agent is selected from at least one of ammonia, ammonium chloride, ammonium nitrate and citric acid.

9. The preparation method according to claim 6, characterized in that, The preparation method further includes post-processing, which includes: The slurry obtained from the reaction system is placed in an aging container for aging treatment to obtain an aged product; The aged product is subjected to a first filtration process to obtain a first filter cake; an alkaline solution is added to the first filter cake for slurry treatment to obtain a slurry product; the concentration of the alkaline solution is 0.1 mol / L-10 mol / L, and the type of alkaline solution includes liquid alkali; The pulping product is subjected to a second filtration process to obtain a second filtered product. The second filtered product is dried, sieved, and demagnetized to obtain a ternary precursor.

10. A battery, characterized in that, This includes the ternary precursor as described in any one of claims 1-5 or the ternary precursor prepared by the preparation method as described in any one of claims 6-9.